2009
DOI: 10.1159/000209230
|View full text |Cite
|
Sign up to set email alerts
|

Genipin Cross-Linked Fibrin Hydrogels for in vitro Human Articular Cartilage Tissue-Engineered Regeneration

Abstract: Our objective was to examine the potential of a genipin cross-linked human fibrin hydrogel system as a scaffold for articular cartilage tissue engineering. Human articular chondrocytes were incorporated into modified human fibrin gels and evaluated for mechanical properties, cell viability, gene expression, extracellular matrix production and subcutaneous biodegradation. Genipin, a naturally occurring compound used in the treatment of inflammation, was used as a cross-linker. Genipin cross-linking did not sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
68
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(75 citation statements)
references
References 102 publications
6
68
0
1
Order By: Relevance
“…Introduction of additional crosslinks in the fibrin gels with crosslinking agents like glutaraldehyde lowers pore size as well as susceptibility to proteolysis [33,66,67]. Genipin, isolated from Gardenia jasminoides fruits, was used successfully by Dare et al [68] as a less toxic alternative to glutaraldehyde for crosslinking of fibrin matrices and induce chondrogenic differentiation of human primary articular chondrocytes. Sell et al [69] crosslinked electrospun fibrinogen scaffolds with three bi-fuctional reagents-glutaraldehyde, 1-ethyl-3-(3, di-methyl aminopropyl) carbodiamide (EDC) and genipin and investigated their peak stress modulus and in vitro degradation.…”
Section: Use Of Bifunctional Reagentsmentioning
confidence: 99%
“…Introduction of additional crosslinks in the fibrin gels with crosslinking agents like glutaraldehyde lowers pore size as well as susceptibility to proteolysis [33,66,67]. Genipin, isolated from Gardenia jasminoides fruits, was used successfully by Dare et al [68] as a less toxic alternative to glutaraldehyde for crosslinking of fibrin matrices and induce chondrogenic differentiation of human primary articular chondrocytes. Sell et al [69] crosslinked electrospun fibrinogen scaffolds with three bi-fuctional reagents-glutaraldehyde, 1-ethyl-3-(3, di-methyl aminopropyl) carbodiamide (EDC) and genipin and investigated their peak stress modulus and in vitro degradation.…”
Section: Use Of Bifunctional Reagentsmentioning
confidence: 99%
“…Recently, Dare et al fabricated a genipin cross-linked human fibrin hydrogel system as a scaffold for articular cartilage tissue engineering. Their results showed that genipin appeared to inhibit the inflammatory reaction observed 3 weeks after subcutaneous implantation of the fibrin hydrogel into rats (Dare et al 2009). Our results were in agreement with their reports showing that the repair site did not result in the inflammation during experimental period.…”
Section: In Vivo Studymentioning
confidence: 99%
“…Numerous studies have focused on tissue-engineering the condylar cartilage and the disc of the TMJ [Almarza and Athanasiou, 2004;Detamore and Athanasiou, 2005;Dare et al, 2009;Hillel et al, 2009;Morotomi et al, 2012]. This study, for the first time, focused on creating a tissueengineered SM of the TMJ with an original method, because we hold that an SM with abnormal function will cause continuous damage to the cartilage and disc rather than nourish them.…”
Section: Discussionmentioning
confidence: 99%